Atypical Sweet syndrome: skin sinus tracts in an acutely febrile patient after lymphoma treatment: a case report - Lu, Shi-Ying; Yang, Hui-Fang; Zeng, Qing-Li; Chen, Peng; Chen, Li; Gao, Jing; Gu, Xue-Kui; Lan, Hai; Luo, Man (Frontiers in Immunology, 2023)
Sweet syndrome (SS) is an uncommon inflammatory disease that involves painful skin, edematous, red papules, plaques, or nodules often accompanied by fever and leukocytosis. SS has three subtypes, including classical, malignant-tumor associated, and drug-induced SS (DISS). Patients with DISS have clear histories of recent drug exposure. The incidence of SS is high in hematological malignancy but rare in lymphomas. Glucocorticoid treatment is the recommended treatment for all subtypes of SS. This case study describes a male patient who had a history of sALCL(Systemic anaplastic large cell lymphoma) and was treated with multiple cycles of monoclonal-antibody (mAb) therapy. They also received the G-CSF injection at the site where skin lesions later developed. They met the diagnosis criteria for DISS, which was considered to be caused by the G-CSF injection. In addition, BV(Brentuximab vedotin) administration might predispose them to DISS. This case illustrates the first reported SS during the lymphoma treatment, with rare clinical presentations of local crater-like suppurative skin lesions. This case expands the available literature on SS and hematologic neoplasms and reminds clinicians to promptly recognize and diagnose SS to minimize patient morbidity and long-term sequelae.